Kedudukan dan Pengakuan Hak Ulayat dalam Sistem Hukum Agraria Nasional - Ilyas Ismail (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: This article aim is to describe concerning the existency of customary rights to the land for the further named hak ulayat in the structure of the power rights acces to the land. The requirements so that it can be recognized as hak ulayat to the land based on the national agrarian law. The study in tihis article is a normative study by using analyse any kind of nasional law, research result and also the expert insight in relation to issue studied. The analyse result shows that hak ulayat in which as the Indiginous rights has position as an entity of rights to the land in Indonesia’s agrarian national law. The rights of those indigenous peopleis recognized its existency if it fulfills two requirements cumulatively are as follow: 1) that indigenous people’s rights are still available/exist, not have ever been, and 2) The application of those rights of indigenous people has to be pro- to Indonesia’s insight. The symbolization of the state recognition to rights of indigenous people is: 1) the legalization into regional law (Qanun) in Districts level; or president decree depends on the location of that indigenous right present; or in kind of related regional leader decree, 2) compensation for hak ulayat which is used for public and even personal needs/interrest.    The Structure and Recognation of Customary Rights to the Land / Hak Ulayat on Indonesia’s Agrarian National Legal System